2017
DOI: 10.1111/jan.13298
|View full text |Cite
|
Sign up to set email alerts
|

Home‐care nursing staff in self‐directed teams are more satisfied with their job and feel they have more autonomy over patient care: a nationwide survey

Abstract: This study suggests that home-care organizations should consider the use of self-directed teams as this increases nursing staff's job satisfaction and may therefore help to retain nursing staff in home care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…Furthermore, the OFG discussions showed that home‐care nurses often find working in a self‐directed team attractive, a finding that is backed up by other research (Gray et al., ; Maurits et al., ; Tjepkema, ). Home‐care nurses in self‐directed teams experience shared responsibility and the freedom to make decisions about the organisation of care, which is associated with the concept of organisational autonomy.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Furthermore, the OFG discussions showed that home‐care nurses often find working in a self‐directed team attractive, a finding that is backed up by other research (Gray et al., ; Maurits et al., ; Tjepkema, ). Home‐care nurses in self‐directed teams experience shared responsibility and the freedom to make decisions about the organisation of care, which is associated with the concept of organisational autonomy.…”
Section: Discussionmentioning
confidence: 64%
“…With regard specifically to organisational autonomy, the rise of self‐directed teams in western countries is an interesting trend (Gray, Sarnak, & Burgers, ; Maurits, De Veer, Groenewegen, & Francke, ; Tjepkema, ). A “self‐directed team” can be described as a team of home‐care nurses that organises nursing care independently, in an optimum way for their patients and without directions from a manager.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, district nurses in the UK (HCNs with a specialist qualification), who are the foundation of the home health system, have also experienced 18% funding cuts since 2010, which has led to service redesign to address growing service demands (Morris, ). Additionally, many Western European countries are facing HCN shortages to meet population needs (Maurits, Veer, Groenewegen, & Francke, ). Given this fiscal climate and the contributions of HCN, optimising the existing workforce is essential to ensure that care is not compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Krietzer and colleagues argue that dissatisfaction in the US nursing workforce is related to bureaucratic structures, poor working conditions, and a loss of autonomy which has led to shortages in the workforce (Kreitzer, Monsen, Nandram, & De Blok, ). In contrast, an innovative self‐directed nursing team model of care—Buurtzorg—developed in the Netherlands has shown to increase nursing satisfaction and a sense of autonomy over patient care, particularly for nursing assistants and bachelor's degree prepared nurses (Maurits et al, ). These autonomous nurse‐led teams have been shown to spend little time on administration by using computerised systems, make local connections, and support continuity in care (Dharamshi, ; Sheldon, ).…”
Section: Discussionmentioning
confidence: 99%